TNF-a and Autoimmunity in chronic rgeumatic heart disease - Muhaimen, Nidhal Abdul; Al kaabi, Zaman I. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: we know that TNF-a which is consider an important inflammatory cytokine mediate the inflammatory reactions which occur in the tissues against the infections agents and other causes of inflammation therefore, here we try to study the role of TNF-a in chronic Rheumatic heart disease and the relationship of TNF-a with extent of histopathological.